TANGGUNG JAWAB PEMERINTAH DAERAH KABUPATEN JEMBER DALAM MENYELENGGARAKAN PENGELOLAAN SAMPAH BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2008 TENTANG PENGELOLAAN SAMPAH: Responsibilities of the Local Government of Jember Regency in Implementing Waste Management Based on Law Number 18 of 2008 Concerning Waste Management - Firman Sulistiyono (UIN Kiai Haji Achmad Siddiq Jember, 2022)
One of the environmental problems that until now has not been handled properly, one of which is waste management. Based on Law No. 18 of 2008 Article 9 there is a responsibility for local governments to organize waste management based on norms, standards, procedures and criteria. Regional government responsibilities are also regulated in Government Regulation Number 81 of 2012 concerning Management of Household Waste and Household-like Waste. With the enactment of the regulations above, local governments have the responsibility to organize waste management, so that environmental pollution can be handled properly. Therefore this paper is intended to examine the actions of the Regional Government in carrying out waste management, research is carried out using normative law, namely research on legal norms. Principles, concepts and theories related to waste management according to law number 18 of 2008. The results of the study show that in carrying out waste management actions local governments often carry out planning actions, control arrangements and supervision. On the other hand, the regional government in handling waste management, until now still refers to Regional Regulation No. 4 of 2011 concerning Waste Management Retribution. Even though there are no regulations governing comprehensive waste management, the Regional Government continues to manage its waste Keywords: Responsibility, Authority, Waste Management. Salah satu masalah lingkungan hidup yang sampai saat ini belum dapat ditangani secara baik salah satunya pengelolaan sampah. Berdasarkan Undang – Undang Nomor 18 Tahun 2008 Pasal 9 terdapat adanya tanggung jawab pemerintah daerah untuk menyeleggarakan pengelolaan sampah berdasarkan norma, standar, prosedur, dan kreteria. Tanggung jawab pemerintah daerah juga diatur dalam Peraturan Pemerintah Nomor 81 Tahun 2012 Tentang Pengelolaan Sampah Rumah Tangga Dan Sampah Sejenis Sampah Rumah Tangga. Dengan berlakunya peraturan diatas pemerintah daerah memiliki tanggung jawab menyelenggarakan pengelolaan sampah, sehingga pencemaran lingkungan hidup bisa tertangani dengan baik. Oleh karena itu tulisan ini dimaksudkan untuk mengkaji tindakan Pemerintah Daerah dalam menyelenggarakan pengelolan sampah, Penelitian dilakukan menggunakan hukum normative, yaitu penelitian terhadap norma-norma hukum. Asas-asas, konsep dan teori yang berkaitan dengan tanggung jawab pemerintah daerah dalam menyelenggarakan pengelolaan sampah menurut undang-undang nomor 18 Tahun 2008. Hasil penelitian menunjukan bahwa dalam melakukan tindakan pengelolaan sampah pemerintah daerah kerap melakukan tindakan perencanaan, pengaturan penegndalian dan pengawasan. Disisi lain, pemerintah daerah dalam melakukan penanganan Pengelolaan sampah, sampai saat ini masih mengacu kepada Perda Nomor 4 Tahun 2011 Tentang Retribusi Pengelolaan Sampah. Meski belum ada peraturan yang mengatur pengelolaan sampahnya secara komprehensif Pemerintah Daerah kabupaten jember tetap melakukan pengelolaan sampahnya. Kata Kunci: Tanggung Jawab, Kewenangan, Pengelolaan Sampah.